Type of TP53 mutation influences oncogenic potential and spectrum of associated K‐ras mutations in lung‐specific transgenic mice. Issue 9 (13th April 2019) - Duan, Wenrui; Gao, Li; Kalvala, Arjun; Aguila, Brittany; Brooks, Christopher; Mo, Xiaokui; Ding, Haiming; Shilo, Konstantin; Otterson, Gregory A.; Villalona‐Calero, Miguel A.
Abstract : TP53 and K‐ras mutations are two of the major genetic alterations in human nonsmall cell lung cancers. The association between these two genes during lung tumorigenesis is unknown. We evaluated the potential of two common Type I (273H, contact) and Type II (175H, conformational) TP53 mutations to induce lung tumors in transgenic mice, as well as K‐ras status, and other driver mutations in these tumors. Among 516 (138 nontransgenic, 207 SPC‐TP53‐273H, 171 SPC‐TP53‐175H) mice analyzed, 91 tumors, all adenocarcinomas, were observed. Type II mutants developed tumors more frequently (as compared to nontransgenics, p = 0.0003; and Type I, p = 0.010), and had an earlier tumor onset compared to Type I ( p = 0.012). K‐ras mutations occurred in 21 of 50 (42%) of murine lung tumors sequenced. For both the nontransgenic and the SPC‐TP53‐273H transgenics, tumor K‐ras codon 12–13 mutations occurred after 13 months with a peak incidence at 16–18 months. However, for the SPC‐TP53‐175H transgenics, K‐ras codon 12–13 mutations were observed as early as 6 months, with a peak incidence between the ages of 10–12 months. Codons 12–13 transversion mutations were the predominant changes in the SPC‐TP53‐175H transgenics, whereas codon 61 transition mutations were more common in the SPC‐TP53‐273H transgenics. The observation of accelerated tumor onset, early appearance and high frequency of K‐ras codon 12–13 mutations in the Type II TP53‐175H mice suggests an enhanced oncogenic function of conformational TP53 mutations, and gains in early genetic instability for tumors containing these mutations compared to contact mutations. Abstract : What's new? Mutations in TP53 and K‐ras frequently occur in non‐small cell lung cancer. Interactions between these two genes during lung tumorigenesis, however, are unknown. Here, contact‐(273H) and conformational‐(175H) mutations in TP53 were investigated for their role in lung tumorigenesis and for associations with K‐ras mutations. In TP53 ‐273H mice, transition mutations in K‐ras codon 61 dominated. Meanwhile, in TP53 ‐175H transgenic mice, transversion mutations in codons 12‐13 were the primary changes. K‐ras codon 12‐13 mutations occurred at a relatively early age in TP53‐175H mice, which also experienced accelerated lung cancer onset. The findings suggest that conformational TP53 mutations possess enhanced tumorigenic potential.